pH-Metric Study of Metal-Ligand Stability Constants of Co(II) , Cu(II) and Zn(II) Complexes with Substituted β-Diketones - S. Bodkhe, Pravin; Patil, K.N.; Narwade, M.L.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
The interactions of Co(II), Cu(II) and Zn(II) with 1-(2' -hydroxy-5'chlorophenyl)- 3( 4' -chlorophenyl)- 1 ,3-propanedione (1) and 1-(2'-hydroxy- 3' -nitro-5' -methylphenyl)-3-( 4' -chlorophenyl)- 1,3-propanedione (2) have been studied by Bjerrurn method as adopted by Calvin and Wilson. The stability constant of 1 : 1 and 1 : 2 complexes of Co(ll), Cu(II) and Zn(II) have been studied at constant temperature (27 ± 0.1 °C ) and 0.1 M ionic strength (NaOH) in 70% dioxane-water mixture. It is observed that formation of 1 : 1 and 1 : 2 complexes is occurring simultaneously